Exegesis of Revelation 20:1-10 About The Millennial Kingdom - Sri Binar; Harman Ziduhu Laia; Widi Prasetyo (Theological Journal Kerugma, 2019)
This paper is about The Millennial Kingdom in Revelation 20: 1-10. By using the exegetical method which has nine steps of analysis (context, literary, structural, grammatical, lexical, historical/conceptual, theological and exegetical), the writer examines the meaning of the phrase inductively. The conclusions obtained are several things, which can be generally described that the phrase thousand years is about the existence of the kingdom of God on earth in the future, literally for a thousand years, where Christ as king was accompanied by his twelve disciples as judges. At that time, the condition of the earth was peaceful because there was no apostasy from Satan.